The impact of macroeconomic factors on OTC derivatives trading values in 2000-2015 - Inovaara, Jussi (fi=Turun yliopisto|en=University of Turku|, 2017)
Over-the-counter derivatives markets have grown extensively in the 21st Century. Bank for International Settlements (BIS) estimates the notional value of outstanding contracts to have increased to USD 493 trillion by 2015, from USD 94 trillion in 2000. The reasons for rapid growth in derivatives trading have been examined mainly from the perspective of the firm. Incentives for hedging with derivatives can be derived from frictions and price-related imperfections on the market. Decreasing the volatility of firm cash flows can affect firm value directly, by lowering financial distress and cost of external funding. Depending on the tax system, also tax incentives may be gained due to increased debt capacity. The thesis uses a nomothetic approach, applying quantitative methods to test the impact of selected macroeconomic factors on derivatives trading values in 2000-2015. Derivatives trading data used is supplied by BIS, and data for factors is from BIS, OECD, and public exchanges. Derivatives asset classes in scope are interest rate, foreign exchange and equity-linked derivatives. Factors used are credit outstanding, changes in interest rates, changes in foreign exchange rates, volatility, economic growth and stock prices. Key findings from multiple regression testing suggest that market movements related to prices, such as interest rates and foreign exchange rates, are not in relation to derivatives trading values measured by notional amounts. On the other hand, total amount of debt on the market is strongly connected with derivatives trading. Also the level of market volatility contributes to interest rate and equity derivatives trading. Economic growth is seen to correlate positively with interest rate derivatives, while results from other asset classes are mixed. Previous literature has examined the relevance of new financial regulation for systemic risk in derivatives markets. The annual volume of netted trades by TriOptima portfolio compression has increased each year, and based on theory, decreases the amount of open trades allowing more sophisticated evaluation of counterparty risk. Main factors driving the use of derivatives are related to the amount of market exposure in firms, such as the amount of debt in the global economy, and foreign trade. Market price factors are mainly irrelevant for trading values. Non-financial companies have an incentive to lower cash flow volatility, and market volatility correlates with the amount of derivatives used. Based on empirical testing, the impact of economic growth varies for each derivatives asset class.